2018
DOI: 10.3389/fncir.2018.00107
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Abnormal Intrinsic Functional Connectivity After Acute Mild Traumatic Brain Injury

Abstract: Mild traumatic brain injury (TBI) is considered to induce abnormal intrinsic functional connectivity within resting-state networks (RSNs). The objective of this study was to estimate the role of sex in intrinsic functional connectivity after acute mild TBI. We recruited a cohort of 54 patients (27 males and 27 females with mild TBI within 7 days post-injury) from the emergency department (ED) and 34 age-, education-matched healthy controls (HCs; 17 males and 17 females). On the clinical scales, there were no s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 67 publications
1
16
1
Order By: Relevance
“…Within the CN, acute mTBI patients showed decreased connectivity in the right CAL in this study. This finding was not consistent with the study of Wang et al, suggesting that acute mTBI patients showed increased FC in the CN 10 …”
Section: Discussioncontrasting
confidence: 99%
“…Within the CN, acute mTBI patients showed decreased connectivity in the right CAL in this study. This finding was not consistent with the study of Wang et al, suggesting that acute mTBI patients showed increased FC in the CN 10 …”
Section: Discussioncontrasting
confidence: 99%
“…Some recent resting-state fMRI BOLD connectivity studies has identified disconnection functional coupling between the prefrontal cortex and these regions [40,41], which are consistent with our results. In addition, the CBF disconnection between the right CPL and bilateral ITG as well as the right FG was also been identified in mTBI patients, suggesting a disruption of the cerebellar-subcortical-cortical loop, which is partly consistent with the previous restingstate functional connectivity studies that indicate the CPL-FG disconnection and the abnormality of the cerebellum network in mTBI [42][43][44]. The disconnection of the cerebellum may be related to the functional deficits in cognitive integration in acute mTBI patients.…”
Section: Neural Plasticitysupporting
confidence: 84%
“…Resting-state fMRI (rs-fMRI), which reflects brain activity while an individual is resting and not performing a specific task, may reveal damage to cognitive function caused by mTBI [10]. Using rs-fMRI, multiple resting-state brain intrinsic networks relevant to the neural mechanisms of mTBI have been demonstrated, such as the default mode network (DMN) [11, 12], executive control network (ECN) [13], and motor network [14]. However, these results were variable due to the application of different approaches to rs-fMRI data analysis and the selection of pre- and post-processing procedures and heterogeneous samples.…”
Section: Introductionmentioning
confidence: 99%